Perancangan Aplikasi Deteksi Orisinalitas File Dokumen Menerapkan Algoritma Ripe-MD 128 - Samsir Samsir (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Detection of the originality of this document file is carried out on text documents to find out changes in the contents of the text in the document and avoid plagiarism or plagiarism of the text. Plagiarism or plagiarism means imitating or imitating or stealing other people's writings and works which are later recognized as one's own writing with or without the permission of the author. Plagiarism of this document file is often applied by academics both at the school and university levels. To overcome the problem, a solution is needed to detect the authenticity of the document file. The process of detecting the originality of this document file uses the Ripe-MD 120 method, where the output is a set of hash values ​​obtained through that method. RIPE-MD was developed for the European Community RIPE project. This improvement and development was carried out because many cryptanalytic efforts had been carried out on RIPE MD-128 and based on the information obtained, RIPE MD-160 was created. RIPE MD-128, the resulting hash value only has a length of 128 bits which is able to detect the authenticity of an image document file.